Interspesific Interactions among Three Species of Deer in Captivity - Setiawan, Erik; Kartono, Agus Priyono; Masy'ud, Burhanuddin (Department of Forest Resources Conservation and Ecotourism - IPB University, 2018)
In natural habitats, every organism including wildlife interacts with another individuals both in one species (intraspecific) and with other species of (interspecific), and each interaction can be positive, negative or neutral. In deer captive breeding of Cariu Bogor, three species of deer were bred namely bawean deer (Axis kuhlii), timor deer (deer timorensis) and spotted deer (Axis axis), but so far the interspecific interaction among the three species has not been known comprehensively. This research was conducted to aim (1) calculate the time usage for activities, (2) calculate the period of space usage and homerange width of each deer species in the captive area, (3) niche breadth and the scores of niche overlap , (4) the characteristic of interspecific interactions, and (5) the presences or absences of cross-breeding among the three deer species that are bred. Data was collected through field observations by recording activity period, time and place of deer presence simultaneously and the attitude or response given by individuals of different deer species, movement mapping and space utilization in four types of habitat also the types of plants consumed, then analyzed with several methods such as Chi-square test, Levins and Hulbert niche width and Morisita index. The results showed that the three deer species had different time and space usage. Most of the time is used for eating and resting in the grasslands. The homerange area of the three deer species are different, where the bawean deer have a wider homerange (3.6 ha) than spotted deer (2.6 ha) and timor deer (2.2 ha). The results of niche breadth calculation showed that the bawean deer had wider niche (4.3) than the spotted deer (2.1) and timor deer (1.6), with the percentage of niches overlap by Morisita index between bawean deer and spotted deer is 95%, between bawean deer and timor deer is 70.5% and between spotted deer and timor deer is 96.6%. Interspecific interaction among the three species is neutral (zero), and there is no crossbreeding between the three species of deer that are bred simultaneously in one breeding area. Keywords: captive breeding, crossbreeding, interspecific interaction, niche overlapping, three deer species